Body dissatisfaction among Iranian youth and adults - Behshid Garrusi; Mohammad Reza Baneshi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: Despite the importance of body satisfaction on one's self image and well-being, little has been written about body image or how it affects people in Iran. The aim of this study is to assess body dissatisfaction and its risk factors in the general Iranian population. The sample size for this cross-sectional study included approximately 1,200 participants (both male and female) and was conducted in 2011. Body dissatisfaction (based on the Figure Rating Scale), demographic characteristics, socioeconomic status, body mass index (BMI) and use of the media were recorded. Nearly two thirds of the participants were included in the middle age group and roughly half of them had a university education. Approximately two thirds of the participants were satisfied with their body. The mean score of body dissatisfaction in women was greater than men (p < 0.0001). Age, gender, marital status and BMI had a significant relationship with body dissatisfaction. The finding of this study demonstrates that in Iran, body dissatisfaction and it consequences must be addressed. While the prevalence and pattern of body dissatisfaction in Iran is as high as other Asian countries, considering cultural variation within Asian countries is also important.